An efficient approach for mining web content sensitivity. (20th August 2009) - Wang, Cheng; Liu, Ying; Jian, Liheng; Zhang, Peng
Abnormal remarks on the web, such as violence, threat, superstition, etc., may disturb the social order and public morality (referred as sensitive content). To provide a quantitative measure of the sensitivity of a webpage, we propose the concept of web content sensitivity which measures how sensitive a page is. We also propose a web content sensitivity mining approach. Our experiment identified a number of sensitive webpages that traditional frequency-based methods failed to find. By varying the sensitive values of the keywords, different sets of high sensitivity keywords were discovered as well as the corresponding webpages.